Dynamic Behavior of Materials, Volume 1 Proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Dynamic Behavior of Materials, Volume 1: Proceedings of the 2010 Annual Conference on Experimental and Applied Mechanics, the first volume of six from the Conference, brings together 71 contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Materials Science, including papers on Composite Materials, Dynamic Failure and Fracture, Dynamic Materials Response, Novel Testing Techniques, Low Impedance Materials, Metallic Materials, Response of Brittle Materials, Time Dependent Materials, High Strain Rate Testing of Biological and Soft Materials, Shock and High Pressure Response, Energetic Materials, Optical Techniques for Imaging High Strain Rate Material Response, and Modeling of Dynamic Response.
Dynamic Material Property Characterization With Kolsky Bars -- Dynamic Triaxial Test on Sand -- Mechanically Similar Gel Simulants for Brain Tissues -- Loading Rate Effect on Tensile Failure Behavior of Gelatins Under Mode I -- On Failure and Dynamic Performance of Materials -- In-situ Optical Investigations of Hypervelocity Impact Induced Dynamic Fracture -- A Dynamic CCNBD Method for Measuring Dynamic Fracture Parameters -- New ""Fish Tank"" Approach to Evaluate Durability and Dynamic Failure of Marine Composites" -- Large Field Photogrammetry Techniques in Aircraft and Spacecraft Impact Testing -- Properties of Elastomer-based Particulate Composites -- Dynamic-tensile-extrusion Response of Polytetrafluoroethylene (PTFE) and Polychlorotrifluoroethylene (PCTFE) -- Dynamic Compression of an Interpenetrating Phase Composite (IPC) Foam: Measurements and Finite Element Modeling -- Improved Mechanical Properties of Nano-nickel Strengthened Open Cell Metal Foams -- A Numerical and Experimental Study of High Strain-rate Compression and Tension Response of Concrete -- Impact Behavior and Dynamic Failure of PMMA and PC Plates -- Experimental Investigation on Dynamic Crack Propagation Through Interface in Glass -- Effect of Temperature and Crack Tip Velocity on the Crack Growth in Functionally Graded Materials -- Characterization of Polymeric Foams Under Muli-axial Static and Dynamic Loading -- Effects of Fiber Gripping Methods on Single Fiber Tensile Test Using Kolsky Bar -- Mechanical Behavior of A265 Single Fibers -- Experimental Study of Dynamic Behavior of Kevlar 49 Single Yarn -- Dynamic Response of Fiber Bundle Under Transverse Impact -- Impact Experiments to Validate Material Models for Kevlar KM2 Composite Laminates -- Numerical Study of Composite Panels Subjected to Underwater Blasts -- Non-shock Initiation Model for Explosive Families-Experimental Results -- Modeling for Non-shock Initiation -- Stress and Strain Analysis of Metal Plates With Holes -- Impact Response of PC/PMMA Composites -- Performance of Polymer-steel Bi-layers Under Blast -- The Blast Response of Sandwich Composites With a Functionally Graded Core and Polyurea Interlayer -- The Blast Response of Sandwich Composites With In-plane Pre-loading -- Laboratory Blast Simulator for Composite Materials Characterization -- Experimental Characterization of Composite Structures Subjected to Underwater Impulsive Loadings -- Controlling Wave Propagation in Solids Using Spatially Variable Elastic Anisotropy -- Constitutive Characterization of Multi-constituent Particulate Composites -- Dynamic Strain Rate Response With Changing Temperatures for Wax-coated Granular Composites -- Strain Solitary Waves in Polymeric Nanocomposites -- Measurement of High-strain-rate Strength of a Metal-matrix Composite Conductor -- A Revisit to High-rate Mode-II Fracture Characterization of Composites With Kolsky Bar Techniques -- The Influences of Residual Stress in Epoxy Carbon-fiber Composite Under High Strain-rate -- Strain Rate-dependent and Temperature- dependent Compressive Properties of 2DCf/SiC Composite -- Compression Behavior of Near-UFG AZ31 Mg-Alloy at High Strain Rates -- Dynamic Torsion Properties of Ultrafine Grained Aluminum -- Effect of Aging Treatment on Dynamic Behavior of Mg-Gd-Y Alloy -- Plasticity Under Pressure Using a Windowed Pressure-shear Impact Experiment -- The Effect of Tungsten Additions on the Shock Response of Tantalum -- Stress Perturbations Caused by Longitudinal Stress Gauges -- Measuring Strength at Ultrahigh Strain Rates -- Shear Stress Measurements in Stainless Steel 2169 Under 1D Shock Loading -- Spall Strength of AS800 Silicon Nitride Under Combined Compression and Shear Impact Loading.-Spallation of 1100-O Aluminum Under Plate Impact Loading -- Line VISAR and Post-shot Metallography Comparisons for Spall Analysis -- Failure of Firefighter Escape Rope Under Dynamic Loading and Elevated Temperatures -- Determination of True Stress-true Strain Curves of Auto-body Plastics -- Elasto-viscoplasticity Behavior of a Structural Adhesive Under Compression Loadings -- Dynamic Behaviors of Fiber Reinforced Aerogel and Mg/Aerogel Composite -- Mechanisms of Slip Weakening and Healing in Glass at Co-seismic Slip Rates -- Rate Dependent Response and Failure of a Ductile Epoxy and Carbon Fiber Reinforced Epoxy Composite -- High Pressure Hugoniot Measurements Using Converging Shocks -- Photonic Doppler Velocimetry Measurements of Materials Under Dynamic Compression -- Dynamic Equibiaxial Flexural Strength of Borosilicate Glass at High Temperatures -- Measurement of Stresses and Strains in High Rate Triaxial Experiments -- A New Technique for Combined Dynamic Compression-shear Test -- A New Compression Intermediate Strain-Rate Testing Apparatus -- A Modified Kolsky Bar System for Testing Ultra-soft Materials Under Intermediate Strain-Rates -- Visualization and Measurements of Wave Propagations in Slurry Hammers -- A Newly Developed Kolsky Tension Bar -- Evaluation of Welded Tensile Specimens in the Hopkinson Bar -- Effect of Aspect Ratio of Cylindrical Pulse Shapers on Force Equilibrium in Hopkinson Pressure Bar Experiments -- Interferometric Measurement Techniques for Small Diameter Kolsky Bars -- Kolsky Bar With a Hollow Incident Tube.
Keywords: Engineering; Mechanics; Mechanics, applied; Materials; Engineering; Theoretical and Applied Mechanics; Mechanics; Materials Science, general